2009
DOI: 10.1016/j.transproceed.2009.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation With Expanded Criteria Donors: The Experience of One Portuguese Center

Abstract: Background. The shortage of kidneys available for transplantation has led to enlarged criteria donors (ECD): namely, donors older than 60 years or aged between 50 and 59 years with 2 of the following characteristics-hypertension, predonation serum creatinine level higher than 1.5 mg/dL or cerebrovascular disease as the cause of death. The aim of this study was to analyze renal transplants using ECD compared with standard criteria donors (SCD) concerning the incidences of delayed graft function (DGF), acute rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
2
14
1
Order By: Relevance
“…There is no consensus on the ultimate effect of short DGF, lasting less than one week, on graft survival; however, when the duration of allograft dysfunction becomes prolonged, the negative effect on kidney graft survival becomes evident [1,2]. The criteria for deceased donors have been expanded because of organ shortages, and consequently DGF has become more common [3,4]. At our center, we have expanded our criteria for acceptable kidney donors since 1995.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on the ultimate effect of short DGF, lasting less than one week, on graft survival; however, when the duration of allograft dysfunction becomes prolonged, the negative effect on kidney graft survival becomes evident [1,2]. The criteria for deceased donors have been expanded because of organ shortages, and consequently DGF has become more common [3,4]. At our center, we have expanded our criteria for acceptable kidney donors since 1995.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of graft failure (e.g., return to maintenance dialysis or graft nephrectomy) is more frequent in marginal donor kidney recipients [6,16,17], as largely documented in recently published series [20][21][22][23][24][25][26][27] (Table 1). Aging of the donors directly impacts on long-term graft survival, and, in a recent series, among 407 KTs, graft survival was significantly lower for the ECD when compared to the non-ECD (5-year survival rate: 74% versus 90%, < 0.001) [21]; the older the donor, the greater seems to be the decrease in survival [6].…”
Section: The ''Marginal Donors''mentioning
confidence: 98%
“…[5][6][7][8][9][10][11] However, kidneys from very young donors are also associated with poor outcome, likely related to technical complications and graft thrombosis. 12 Furthermore, studies have shown that patient survival at the end of the first and third year after transplant were comparable between expanded criteria donors and standard criteria donors [13][14][15] ; however, graft survival and function were significantly worse with increased incidence of delayed graft function (DGF) and acute rejection episodes. 15 Ferrer and associates identified DGF and acute rejection episodes as risk factors for graft failure.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, studies have shown that patient survival at the end of the first and third year after transplant were comparable between expanded criteria donors and standard criteria donors [13][14][15] ; however, graft survival and function were significantly worse with increased incidence of delayed graft function (DGF) and acute rejection episodes. 15 Ferrer and associates identified DGF and acute rejection episodes as risk factors for graft failure. 15 In addition, there are reports concluding that there is no statistical significant correlation between donor age and 5-year graft function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation